Teacher- parent collaboration in two primary schools’ special education integrated programmes: Application of epstein’s framework / Girija Kumari K.S.Nayor - Girija Kumari, K.S.Nayor (2016)
Teacher- Parent Collaboration (TPC) is an important factor for the development of Children with Special Needs (CSN). Dividing the role in school and at home as different entities is not appropriate as children need close monitoring at home too. To enable parents to be actively involved in schools, teachers need to cooperate with parents and develop collaboration between them. The aims of this study were: 1) to explore to what extent TPC was practised during the planning and implementation of activities, 2) to explore factors that supported and inhibited the planning and implementation of the activities, and 3) to explore how the framework advocated by Epstein, involving elements such as parenting, communicating, volunteering, learning at home, decision making and collaborating with community was incorporated in the schools’ activities. This study was a case study. Two schools with the Special Education Integrated Programme (SEIP) were selected and the participants of the study comprised two administrators, four special education teachers and four parents of CSN. The data were obtained through interviews, observations and document analysis. NVivo 10, a computer software programme was used to manage the interview transcripts, the observation notes and summaries of the document analysis. The same software was used to code data and form categories within the case analysis, to produce individual reports, before the cross case analysis was done using the constant comparative technique to identify the emerging themes from the TPC activities. The findings revealed that teachers played a major role in determining and planning the activities for the academic year. The involvement of parents in providing suggestions was noted during the frequent short interactions between the teachers and the parents. The activities planned focused on the needs of CSN, and the parents’ needs were identified through feedback obtained during formal and informal interactions with parents. When iv the activities were implemented, the parents followed the teachers and were involved in carrying out the activities planned although parents collaborating with the teachers were only seen in a few activities, where they took on a passive role in most cases. There were activities that were planned but which were not carried out due to some hindering factors. The study concluded that there was more involvement than collaboration between the teachers and the parents. Other than the elements advocated by Epstein, inter-cultural and inter-spiritual knowledge elements were also evident in the activities planned in the two SEIP. If active collaboration were to be carried out in the schools then there would be a shared responsibility between teachers and parents to ensure quality education for CSN, as envisioned in the Malaysian Education Blueprint.